The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/798967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate-mediated regulation of the arginine transporter ofToxoplasma gondii

Abstract: 14 Intracellular parasites, such as the apicomplexan Toxoplasma gondii, are adept at 15 scavenging nutrients from their host. However, there is little understanding of how 16 parasites sense and respond to the changing nutrient environments they encounter during 17 an infection. TgApiAT1, a member of the apicomplexan ApiAT family of amino acid 18 transporters, is the major uptake route for the essential amino acid L-arginine (Arg) in 19 T. gondii. Here, we show that the abundance of TgApiAT1, and hence the rat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…Based on our findings, and on several other recent studies into Arg uptake in T. gondii [27,31,41], we can now propose a comprehensive model for the uptake of cationic amino acids into these parasites (Fig 7). The scavenging of AA + by parasites results in a depletion of these amino acids in the host cell cytosol, causing upregulation of the host CAT1 AA + transporter [41].…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Based on our findings, and on several other recent studies into Arg uptake in T. gondii [27,31,41], we can now propose a comprehensive model for the uptake of cationic amino acids into these parasites (Fig 7). The scavenging of AA + by parasites results in a depletion of these amino acids in the host cell cytosol, causing upregulation of the host CAT1 AA + transporter [41].…”
Section: Discussionsupporting
confidence: 66%
“…The data in the present study indicate that TgApiAT6-1 functions as this alternative Arg transporter. We have recently shown that the expression of TgApiAT1 is up-regulated under Arg limiting conditions and expressed at low levels under Arg replete conditions [31]. The differential expression of TgApiAT1 may therefore allow these parasites to survive when Arg levels are limited, while TgApiAT6-1 may ensure regulated uptake of Arg and Lys under nutrient rich conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations